Handbook of health economics - Culyer, A. J.; Newhouse, Joseph P. (Amsterdam ; New York : Elsevier, 2000)
"The Handbook of Health Economics" provides an up-to-date survey of the burgeoning literature in health economics.
Includes bibliographical references and indexes.
oif 29/01/15
Loan
Keywords: Medical economics; Economics, medical; Health planning & health management; Health financing; Health economics